PENGARUH KUALITAS SISTEM INFORMASI, KUALITAS INFORMASI, PERCEIVED USEFULNESS, DAN PENGENDALIAN INTERNAL TERHADAP KEPUASAN PENGGUNA SISTEM INFORMASI AKUNTANSI (Studi Empiris terhadap bank BRI di Kabupaten dan Kota Serang) - Noormawati, Linda Septie; Purwanto, Agus (Diponegoro Journal of Accounting, 2024)
The use of technology in a company is very important because technology can be an added value for the company in competing in the business world. The development of information technology today can simplify and shorten the time for users to perform their work. This research is conducted to prove the relationship between the quality of the accounting information system, information quality, perceived usefulness, and internal control with user satisfaction of accounting information systems. The population used in this research is employees of PT Bank Rakyat Indonesia (Persero) TBK in Serang Regency and City. This research had been done with primary data collection methods carried out by distributing questionnaires within a certain time and not continuing. Data collection was carried out by convenience sampling method and 71 samples were obtained. The findings of this study indicate that the quality of accounting information systems, information quality, perceived usefulness, and internal control have a positive and significant effect on the level of satisfaction of Accounting Information System users.